New Linguistic Terms in the Modern Kazakh Language (Eurasian Journal of Philology Science and Education, 2024)
In the modern period, the development of language occurs together with the development of new technologies, scientific spheres of the human mind. Therefore, not only the names of new subjects, but also the names of new concepts in many languages are the reasons for the appearance of a large number of new language units. This article is devoted to the study of modern word-formation trends in the Kazakh language, formed as a result of the influence of the processes of language integration and differentiation.The object of the article's research is the main term-forming methods and models in the Kazakh language. Attention is focused on the need for a comprehensive consideration of the issues of Kazakh terminology, term formation and terminography. The paper emphasizes the need for a comprehensive linguistic study of new and commonly used terms in connection with the political and social changes taking place in society.The purpose of the scientific article is to study and analyze the basic techniques and models of terminology of the national language. To achieve this goal, the following tasks are defined: to analyze the main methods and models of terminology formation in the field of socio-political, social and historical spheres; to study both borrowed and national terms; to describe the functional and usage features of these terms; to identify the main characteristics of borrowed and national terms.It is revealed that the most productive methods of the terminological system are the following: terminization, acceptance of terms from other terminological systems, the combination of suffixes and the formation of term combinations, as well as the most frequent cases of phonomorphological adaptation of international terms and their subsequent use in the Kazakh language.Keywords: word formation, hybrid word formation, derivation, derived words, composites, contamination, principles of terminology, borrowed words, methods of term formation.